2020
DOI: 10.1111/bjhp.12446
|View full text |Cite
|
Sign up to set email alerts
|

Living with persistent insomnia after cancer: A qualitative analysis of impact and management

Abstract: ObjectivesTo conduct a qualitative exploration of the lived experience of insomnia disorder and its management amongst a sample of mixed‐diagnoses cancer survivors.MethodsTwenty‐seven cancer survivors with persistent insomnia were recruited to this qualitative study following completion of treatment for breast (12), prostate (7), colorectal (7), and gynaecological (1) cancers. Eleven males and 16 females (mean age 62 years), who met DSM‐5 criteria for insomnia disorder, contributed to one of four focus group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The finding that sleep disruption is a persistent and troubling problem in this population is consistent with a number of previous studies 9,17 . Indeed, a recent qualitative study in 27 cancer survivors reported that poor sleep was a long-term problem that impacted negatively on quality of life including sociability, physical activity and psychological well-being 48 . Chroinic insomnia is associated with risk of exacerbated morbidity and mortality in cancer patients 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The finding that sleep disruption is a persistent and troubling problem in this population is consistent with a number of previous studies 9,17 . Indeed, a recent qualitative study in 27 cancer survivors reported that poor sleep was a long-term problem that impacted negatively on quality of life including sociability, physical activity and psychological well-being 48 . Chroinic insomnia is associated with risk of exacerbated morbidity and mortality in cancer patients 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant psychopathology symptoms are detected throughout the course of cancer survivorship up to several years post-diagnosis and treatment have been welldocumented, even before the COVID-19 pandemic [31]. Compared with the general population, adult cancer survivors have an increased prevalence of mental health comorbidities including major depressive and anxiety episodes, severe psychological distress, bipolar disorders, obsessive-compulsive disorders, neurocognitive dysfunction and suicidal outcomes [32][33][34][35][36][37][38], as well as other adverse late-effects interdependent with mental illness outcomes such as post-cancer chronic pain, fatigue and sleep disturbances [39][40][41][42][43]. Besides the pre-existing medical conditions at the time of cancer diagnosis [44], many of these chronic condition and multimorbidity clusters are identified following cancer [45,46].…”
Section: The Complexity Of Mental Health and Comorbidities In Cancer Survivorshipmentioning
confidence: 99%
“…with cancer and undergo chemotherapy treatment and continue to experience sleep disturbances because they often wake up in the middle of the night to urinate in the bathroom, anxious, cannot sleep before or after waking up in the middle of the night [20]. Moreover, the patients who have repeatedly received chemotherapy are increasingly at risk of experiencing sleep disorders and insomnia, so they need to be given with therapy to deal with sleep disorders [10].…”
Section: Patients Who Have Recently Been Diagnosedmentioning
confidence: 99%